2013
DOI: 10.1093/nar/gkt058
|View full text |Cite
|
Sign up to set email alerts
|

MiR-10a* up-regulates coxsackievirus B3 biosynthesis by targeting the 3D-coding sequence

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs that can posttranscriptionally regulate gene expression by targeting messenger RNAs. During miRNA biogenesis, the star strand (miRNA*) is generally degraded to a low level in the cells. However, certain miRNA* express abundantly and can be recruited into the silencing complex to regulate gene expression. Most miRNAs function as suppressive regulators on gene expression. Group B coxsackieviruses (CVB) are the major pathogens of human viral myocarditis and dilated car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 46 publications
(48 reference statements)
1
46
0
Order By: Relevance
“…5b). The expression pattern determined by miRNA sequencing was confirmed by taqman RT-qPCR for 2 miRNAs that were described in the literature to be related to enteroviral infection: miR-146a-5p (upregulated) and miR-23b (downregulated) [45][46][47][48] ( Fig. 5c-d).…”
Section: Pattern Of Cellular Mirnas In Ductal-like Cells Persistentlysupporting
confidence: 53%
“…5b). The expression pattern determined by miRNA sequencing was confirmed by taqman RT-qPCR for 2 miRNAs that were described in the literature to be related to enteroviral infection: miR-146a-5p (upregulated) and miR-23b (downregulated) [45][46][47][48] ( Fig. 5c-d).…”
Section: Pattern Of Cellular Mirnas In Ductal-like Cells Persistentlysupporting
confidence: 53%
“…Previous studies provided evidence to support that miRNAs could modulate viral translation through imperfect or perfect binding to the 3= UTR (24), the 5= UTR (25)(26)(27), or the sequences within the coding region (28)(29)(30). The 5= UTR (7), 3= UTR (11,31,32), or coding position locations (7) selected for miRT insertion differed among various viruses depending upon where insertion was tolerated within the particular virus.…”
Section: Discussionmentioning
confidence: 99%
“…149 For example, it was shown that miR-10a* promotes CVB3 biosynthesis by targeting the 3-dimensional coding sequence of CVB3 genomic RNA. 150 Moreover, certain miRNAs were found to contribute to the development of viral myocarditis without evidence of altering viral replication dynamics. One example is miR-21, whose change in expression levels during CVB3 infection is controversial because some studies indicated its upregulation, 70,151 whereas others demonstrate downregulation.…”
Section: Virus-induced Direct Damagementioning
confidence: 99%